Remotely sensed estimation of vegetation shifts in the polar and alpine tree-line ecotone in Finnish Lapland during the last three decades - Franke, Anna; Feilhauer, Hannes; Bräuning, Achim; Rautio, P.; Braun, Matthias (Forest Ecology and Management, 2019)
Global warming is predicted to affect ecosystems, particularly in high-latitude regions where polar amplification accelerates temperature rise and environmental changes. Here, where plants grow under adverse conditions, a warmer climate provides more favourable conditions for growth and regeneration. At the alpine and polar tree line in Finnish Lapland, rising temperatures are assumed to promote densification and expansion of conifers towards fell tops and treeless boreal heathlands beyond the recent tree-line position. In this study, we analysed vegetation changes in the pine treeline ecotone in six study sites in Finnish Lapland using multi-spectral satellite data during 1984–2017. All of the six sites were established in fell areas, covering the transition from closed forest stands of the lower elevations to the open fell tops beyond the treeline position. The southern sites were located in pine dominated-stands, where treelines were of alpine character. The northern sites were located in the polar treeline ecotone where mountain birch forests already dominate the landscape. We assessed shifts in the vegetation pattern of the fell sites using the normalized difference vegetation index (NDVI) and a RandomForest land-cover classification as indicators of potential change. We did not find clear trends for advancing coniferous tree lines towards open fell tops or treeless heath vegetation, neither by NDVI change detection nor by the land-cover classification. However, we found evidence for densification of open forest stands and sparse vegetation cover in lower elevations and the expansion of deciduous vegetation in higher elevations of previously vegetation-free or sparsely covered fell tops. Increasing stand density was detected mostly in the southern, pine-dominated sites, while the northern sites indicated increasing biomass near the fell tops. Prominent changes in vegetation patterns originated rather from human impact in the southern sites appearing as recent roads, clear-cuttings or infrastructure constructions in skiing areas. In the northern sites, distinctive changes arose from human impact or from biotic disturbance events such as moth outbreaks defoliating mountain birch stands at site Karigasniemi.
CRIS-Team Scopus Importer:2019-10-29
Keywords: Climate change; Multi-spectral satellite data; NDVI; Treeline ecotone; Vegetation shifts